Cross-border mergers and acquisitions of multinational firms: New firm-level evidence - Christian Arndt; Anselm Mattes (Institut für Angewandte Wirtschaftsforschung (IAW), 2010)
FDI is an important channel for productivity spillovers across economies. But productivity and employment effects of cross-border mergers and acquisitions (M&A) on multinational firms are rather unclear and much disputed. We empirically analyze the effects of cross-border M&A on the performance of multinationals in Germany using new data on the firm-level. In order to control for possible selection biases we use a propensity score matching approach. We find that, first, foreign-owned multinationals are smaller but more productive than their domestic counterparts in the mean. But controlling for differences in the industrial composition and firm size, foreign-owned multinationals are larger in terms of capital, sales, and value added. The difference of total factor productivity amounts to 6 %. Second, multinationals show quite heterogeneous performances after cross-border M&A. Third, we do not find an average causal effect of cross-border M&A on the employment of the acquired multinational firm. But most importantly, the causal effect of cross-border M&A on the multinationals' productivity is positive and significant.
Keywords: F21; F23; 330; FDI; Spillover; foreign ownership; cross-border M&A; productivity; employment effects; Multinationales Unternehmen; Übernahme; Fusion; Direktinvestition; Produktivität; Spillover-Effekt; Beschäftigungseffekt; Schätzung; Deutschland